Zerowrap: Inovasi Desain Busana Zero Waste Berbasis Filosofi Mummy Wrap - Tri Hadinico, Assyifa; Wahyuningsih, Urip (Pusat Penerbitan LPPM ISI Bali, 2025)
This study explores Zerowrap, an innovative sustainable fashion design concept that merges the ancient Egyptian mummy wrap philosophy with the principles of zero waste fashion design. The main objective of this project is to create a garment that maximizes material efficiency, upholds ecological responsibility, and embodies strong aesthetic value. Employing a qualitative-descriptive approach with an experimental design method, the research focuses on the creative process from the conceptual to the production stage. These stages include visual exploration, moodboard development, material selection, design formulation, and the application of zero waste pattern cutting techniques. Linen was chosen as the primary material for its durability, natural fiber composition, biodegradability, and alignment with sustainable design principles. The results demonstrate that zero waste pattern cutting effectively eliminates textile waste by utilizing every inch of fabric. Moreover, leftover pieces were repurposed into decorative details such as ribbons and floral accents, enhancing the garment’s aesthetic appeal while reinforcing its ecological message. Visually, the Zerowrap design features asymmetric wrappings in red and pink hues, symbolizing strength and tenderness an expression of balance between function, form, and symbolic meaning. The reinterpretation of the mummy wrap serves as a metaphor for human care and responsibility toward environmental sustainability, where each piece of fabric holds both purpose and meaning. Ultimately, Zerowrap represents more than just an artistic and functional garment; it stands as a reflective medium that promotes ecological awareness and social responsibility within the contemporary fashion industry. This project affirms that zero waste design is not only a technical approach but also an innovative strategy to foster a more ethical, creative, and sustainable fashion system.